Refleksi Budaya dalam Konstruksi Ungkapan Peribahasa (Analisis Komparatif Budaya Arab dan Indonesia dalam Ungkapan Peribahasa Bermakna Sepadan) - Yasmin Azizi; Insanul Hasan; Latifa Islami Anuar; Adjie Prasetio Utama; Miftahul Ilmi (Diwan: Jurnal Bahasa dan Sastra Arab, 2018)
This article discusses the differences between Arabic and Indonesian cultures represented in the construction of proverbial expressions. The result of the research proves that cultural phenomena are reflected in Arabic and Indonesian proverbs. Two different proverb expressions that have similar meanings are proven to represent two different cultures. The expression of Arabic proverbs which the author has identified reflects the culture of the ignorant Arab society used to have a war, compose poems and literatures, have the culture of trade, and have food typical of Arab society. Besides, the authors identify that the expression of Indonesian proverbs reflects the culture of the community that has a maritime and agrarian-based livelihood source. The cultural phenomenon in the proverb expression is represented by the choice of words used to construct it.